PARADIGM OF ONLINE LEARNING IN HIGHER EDUCATION: PARADIGMA PEMBELAJARAN ONLINE DI PENDIDIKAN TINGGI - Salaki Reynaldo Joshua; Yuri Vanli Akay; Kenneth Yosua Rumawas Palilingan; Henry Valentino Florensius Kainde; Heilbert Armando Mapaly; Salvius Paulus Lengkong (Pusat Riset dan Inovasi Nasional, 2022)
The Role of Information and Communication Technology is currently very influential in supporting the various activities undertaken by humans. Universities as a place to produce great human resources constantly looking for innovations to how it can be generate good quality resources through qualified teaching staff, support facilities, and even methods of learning of interest to learners. Good learning process certainly affect the learning conditions of students. In answer to the current challenges must be found appropriate solutions and to answer the needs that exist. Online learning is a learning paradigm that is currently used by college as a one of the solutions in the learning process is carried out in universities. Online learning as based learning online provides convenience in the process of teaching and learning to lecturers and students at the University.